2019
DOI: 10.1039/c9ra06662d
|View full text |Cite
|
Sign up to set email alerts
|

Process parameter sensitivity investigation on the reaction crystallization production of K2SO4 with salt lake leonite ore

Abstract: Reaction crystallization process optimization for the production of K2SO4 with low-grade salt lake leonite ore in Qinghai, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The process parameters of the material ratio, water addition, and operating temperature are sensitivity for the objective of product purity and recovery. 8 From the reactions of eqn ( 1)-( 3), we found that the amount of water is critical to the decomposition process of carnallite in an aqueous solution. Usually, the detection and assessment of the reactive process of carnallite decomposition are operated by analyzing the entire chemical compositions of E(L) or F(L).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The process parameters of the material ratio, water addition, and operating temperature are sensitivity for the objective of product purity and recovery. 8 From the reactions of eqn ( 1)-( 3), we found that the amount of water is critical to the decomposition process of carnallite in an aqueous solution. Usually, the detection and assessment of the reactive process of carnallite decomposition are operated by analyzing the entire chemical compositions of E(L) or F(L).…”
Section: Introductionmentioning
confidence: 98%
“…6 A source of KCl is the carnallite double salt, which has the composition KCl$MgCl 2 $6H 2 O or KMgCl 3 $6H 2 O, and is either obtained as the ore or recovered from brine that favors carnallite. [7][8][9] Carnallite is treated with fresh water to dissolve MgCl 2 and keep KCl in the crystalline state. Then, KCl otation from the mixed salts is carried out using an amine as the collector.…”
Section: Introductionmentioning
confidence: 99%